THEORETICAL BASIS OF THE REGIONAL DIMENSION OF INTERNATIONAL RELATIONS (Journal of Oriental Studies, 2018)
The article considers the features of the regionalization of modern international relations, the formation of regions and the theoretical measurement of these processes by the theorists of the «old» and «new» regionalism. Examples of «European» and «Asian» regionalism compare the features of regional processes in different civilization environments. A comparative analysis of the formation, foundations and evolution of the most important theories of regionalism is carried out. The theory of regional security complexes was first presented in the works of the Copenhagen School. In their studies, the school representatives attempted to define regional security, its structure, the dynamics of development and transformation of approaches to national and global security, translating them into a regional plane. In their opinion, it is the region that is the place where the two spheres of security (national and global) interact and where the main events and actions take place. This theory is not indisputable, but it allows us to analyze regional dynamics and the construction of a global security complex through a region prism.